Promosi kesehatan melalui edukasi dan pelayanan skrining kesehatan terpadu pada pasangan usia subur dan lansia - Pipin, Apriliana; Lina, Anastasia; Wijayati, Therecia; Trivina, Trivina (JOURNAL of Public Health Concerns, 2026)
Background: The community midwifery approach places women, families, and communities at the center of health services throughout the life cycle through the principle of a continuum of care. Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, dyslipidemia, and hyperuricemia are major risk factors contributing to increased morbidity and mortality, and pose a challenge to achieving Sustainable Development Goals (SDGs) Goal 3. Low screening coverage and public knowledge, particularly among couples of childbearing age and the elderly, have the potential to cause delays in the detection and prevention of NCDs. Purpose: To improve health knowledge through education and integrated midwifery-based health screening services for couples of childbearing age and the elderly as an effort to detect and prevent NCDs early. Method: A community service activity was conducted on November 9-10, 2025, at the Salib Suci Church, targeting 42 church members who participated in health education activities, specifically related to general health, specifically health screening efforts. This activity was a midwifery-based health promotion activity. Knowledge levels were categorized as good, sufficient, and poor. Evaluation of activities is carried out by looking at the analysis of descriptive measurement results between the pre-test and post-test. Results: Data obtained on respondents' knowledge levels regarding health screening before the educational activity was categorized as good (19.0%), sufficient (54.8%), and poor (26.2%). There was an increase in respondents' knowledge after the educational activity, with 38.1% of respondents in the good category, 54.8% in the sufficient category, and 7.1% in the poor category. Conclusion: The educational activity and integrated midwifery-based health screening services, which included blood pressure, blood sugar, cholesterol, and uric acid tests for fertile couples and the elderly, have been shown to have a positive impact on increasing community knowledge levels. Integrating health screening with education is an effective approach in community service activities, while also supporting promotive and preventive efforts in the early prevention of non-communicable diseases at the community level. Suggestion: Integrated midwifery-based health screening services need to be implemented sustainably and integrated with routine community health center programs to further enhance the impact of increasing public health knowledge and awareness. It is also recommended that future community service activities include follow-up in the form of individual counseling, referrals for at-risk cases, and monitoring of changes in health behavior to strengthen outcomes and provide long-term benefits to the community. Keywords: Childbearing age; Early prevention; Elderly; Health promotion; Integrated health screening; Non-communicable diseases Pendahuluan: Pendekatan kebidanan komunitas menempatkan perempuan, keluarga, dan komunitas sebagai pusat pelayanan kesehatan sepanjang siklus kehidupan melalui prinsip continuum of care. Penyakit Tidak Menular (PTM) seperti hipertensi, diabetes melitus, dislipidemia, dan hiperurisemia merupakan faktor risiko utama yang berkontribusi terhadap meningkatnya morbiditas dan mortalitas, serta menjadi tantangan dalam pencapaian Sustainable Development Goals (SDGs) tujuan ke-3. Rendahnya cakupan skrining dan pengetahuan masyarakat, khususnya pada pasangan usia subur (PUS) dan lansia, berpotensi menyebabkan keterlambatan deteksi dan pencegahan PTM. Tujuan: Untuk meningkatkan pengetahuan kesehatan melalui edukasi dan pelayanan skrining kesehatan terpadu berbasis kebidanan pada pasangan usia subur dan lansia sebagai upaya deteksi dini dan pencegahan penyakit tidak menular. Metode: Kegiatan pengabdian kepada masyarakat dilaksanakan pada 9-10 November 2025 di lingkungan Gereja Salib Suci, dengan sasaran 42 umat gereja yang mengikuti kegiatan edukasi kesehatan, khususnya terkait kesehatan secara umum dalam hal ini upaya skrining kesehatan. Kegiatan ini merupakan promosi kesehatan berbasis kebidanan. Tingkat pengetahuan dikategorikan menjadi baik, cukup, dan kurang. Evaluasi kegiatan dilakukan dengan melihat analisa hasil pengukuran deskriptif antara pre-test dan post-test. Hasil: Mendapatkan data tingkat pengetahuan responden tentang skrining kesehatan sebelum kegiatan edukasi yang dalam kategori baik sebesar 19.0%, kategori cukup sebesar 54.8%, dan kategori kurang sebesar 26.2%. Terjadi peningkatan pengetahuan responden setelah kegiatan edukasi menjadi dalam kategori baik sebesar 38.1%, kategori cukup sebesar 54.8%, dan kategori kurang sebesar 7.1%.  Simpulan: Kegiatan edukasi dan pelayanan skrining kesehatan terpadu berbasis kebidanan melalui pemeriksaan tekanan darah, gula darah, kolesterol, dan asam urat pada pasangan usia subur dan lansia terbukti memberikan dampak positif terhadap peningkatan tingkat pengetahuan masyarakat. Integrasi skrining kesehatan dengan edukasi merupakan pendekatan efektif dalam kegiatan pengabdian kepada masyarakat, sekaligus mendukung upaya promotif dan preventif dalam pencegahan dini penyakit tidak menular di tingkat komunitas. Saran: Pelayanan skrining kesehatan terpadu berbasis kebidanan perlu dilaksanakan secara berkelanjutan dan terintegrasi dengan program rutin puskesmas agar dampak peningkatan pengetahuan dan kesadaran kesehatan masyarakat dapat menjadi semakin baik. Kegiatan pengabdian selanjutnya juga disarankan untuk menambahkan tindak lanjut berupa konseling individual, rujukan bagi kasus berisiko, serta pemantauan perubahan perilaku kesehatan guna memperkuat luaran dan memberi manfaat jangka panjang bagi masyarakat.